VISITING PROFESSOR PROGRAM: IS IT EFFECTIVE IN IMPROVING STUDENTS’ COMPETENCE? - Beleven Khrismawan; Aulia Luqman Aziz; Dini Kurnia Irmawati (Erudio Journal of Educational Innovation, 2021)
Universities all around the globe have been working hard on internationalization to improve the quality of education, students, and alumni, along with the demand of a more dynamic world. Universitas Brawijaya (UB), as one of the renowned campuses in Indonesia, has also implemented the internationalization strategy to realize its vision and mission as a World Class, Entrepreneurial University. As part of the internationalization strategy, UB runs a “3 in One” program involving visiting professors from universities abroad, practitioner lecturers, and internal lecturers in education, research, and community service activities. This study aimed to evaluate the implementation of the “3 in One” program, emphasizing lecturers’ perspectives as program implementers. We employed a mixed-method study with a qualitative and quantitative approach. The research population was all lecturers involved in the “3 in One” Program. Samples were chosen using stratified random sampling. The research instrument was a questionnaire adapted from (a) the Guidebook of World Class Professors by the Directorate General of Resources for Science, Technology, and Higher Education of the Ministry of Research, Technology, and Higher Education and (b) the Term of Reference (TOR) of the 2019 “3 in One” Program of UB, Student Evaluation of Educational Quality (SEEQ), and (c) semi-structured interviews. It is expected that our findings could become a reference for stakeholders of UB to evaluate and improve the program. In addition, the findings could also become a creative reference for the government and other universities in Indonesia to adopt a similar program according to institutional needs.